Pengaruh Penerapan Sistem Akuntansi dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan Daerah: Studi Kasus pada Badan Keuangan dan Aset Daerah Kabupaten Gorontalo - Armiati; Amir Lukum; Victorson Taruh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Regional government financial statements play a crucial role in developing regional government accountability. Thus, it must be quality as it will determine its possibility to be a reference of policy-making and beneficial for its users. This research aims to determine the influence of implementing an accounting system and human resource competency on the quality of regional financial statements at the Regional Financial and Asset Agency of Gorontalo Regency. This research uses a descriptive quantitative. The samples were determined through purposive sampling. This research uses primary data by distributing questionnaires to 41 respondents who manage financial statements. Then, the data are analyzed using multiple linear regression. The results showed that 1) the accounting system has a positive and significant influence on the quality of financial statement, 2) human resource competence has a positive and insignificant influence on the quality of financial statement, and 3) the accounting system and human resource competence simultaneously have a significant influence on the quality of financial statement at the Gorontalo Regency Regional Financial and Asset Agency.